Reconceptualizing Context: A Multilevel Model of the Context of Reception and Second‐Generation Educational Attainment. Issue 3 (September 2018) - Luthra, Renee; Soehl, Thomas; Waldinger, Roger
This paper seeks to return scholarly attention to a core intellectual divide between segmented and conventional (or neo‐)assimilation approaches, doing so through a theoretical and empirical reconsideration of contextual effects on second‐generation outcomes. We evaluate multiple approaches to measuring receiving country contextual effects and measuring their impact on the educational attainment of the children of immigrants. We demonstrate that our proposed measures better predict second‐generation educational attainment than prevailing approaches, enabling a multilevel modeling strategy that accounts for the structure of immigrant families nested within different receiving contexts.